A motion capture system using passive markers - Sementille, Antonio Carlos [UNESP]; Lourenço, Luís Escaramuzi; Rodello, Ildeberto; Brega, José Remo Ferreira [UNESP] (Association for Computing Machinery (ACM), 2004)
This article describes a marker-based optical tracking system using a single camera for determining the positioning and orientation of the body joints. In this implementation, ARToolkit library as well as an approach was used in order to increase the reliability of a motion capture system by using a simplified anatomical human model.
Keywords: Artoolkit; Motion capture; Optical tracking